Consent: gender, power and subjectivity - James-Hawkins, Laurie; Ryan-Flood, Róisín (Transformations, 2024)
"This book explores the concept of consent in different contexts with an aim toward exploring the nuances of what consent means to different people and in different contexts. While it is generally agreed that consent is a fluid concept, legal and social attempts to explain the meaning of consent often centre on overly simplistic, narrow and binary definitions and to view consent as something that occurs at a specific point in time. This book examines the nuances of consent and how it is enacted and re-enacted in different settings (including online spaces) and across time. Consent is most often connected to the idea of sexual assault and is often viewed as a straight-forward concept and one that can be easily explained. Yet there is confusion among the public, as well as among academics and professionals as to what consent truly is and even the degree to which individuals conceptualise and act on their own ideas about consent within their own lives. Topics covered include: consent in digital and online interactions, consent in education, consent in legal settings and the legal boundaries of consent, and consent in sexual situations including sex under the influence of substances, BDSM, and kinky sex. This book will appeal to students and scholars interested in issues of consent from the social sciences, gender theory, feminist studies, law, psychology, public health, and sexuality studies"--